Soft actuators and their fabrication for bio-inspired mobile robots - Lau, Gih-Keong (2016)
Dielectric elastomer actuators (DEA), which are capable of muscle-like actuation, have potential to drive insect-inspired flapping-wing robotfly. They have not been successfully used to drive flapping wings due to various limitations. This paper revisits their use and integration in a thoracic mechanism as either indirect or direct muscles. Three forms of DEA, namely, folded, rolled, and pre-stretched membrane, were evaluated and integrated in different thoracic mechanisms. The pre-strained membrane of dielectric elastomer was found capable of generating a large rotation. On the other hand, the folded and rolled ones with either no or little pre-strain performed modestly in this flapping-wing application. Pre-strain was found to be important to maximize the actuator performance. In addition, this paper reviewed manufacturing processes for multi-layered DEAs and possibility of introducing pre-strained in the multi-layered layup.